Peculiarities of Charge Transfer in SiO2(Ni)/Si Nanosystems - Egor Yu. Kaniukov; Dzmitry V. Yakimchuk; Victoria D. Bundyukova; Alena E. Shumskaya; Abdulkarim A. Amirov; Sergey E. Demyanov (Advances in Condensed Matter Physics)
This work is devoted to study the peculiarities of charge transfer in SiO2(Ni)/Si nanosystems formed as a result of the electrochemical deposition of nickel into the pores of the ion-track silicon oxide template on silicon. Special attention is given to analysis of the results in the context of the band structure and physical properties of dielectric on semiconductor systems with metallic inclusions in the dielectric matrix. Experimental studies of the current-voltage characteristics of SiO2(Ni)/Si nanostructures demonstrated that value of potential barrier on the Si/metal interface in the pores of the silicon oxide template depended on temperature. On the basis of these results an interpretation of the charge transfer mechanisms in SiO2(Ni)/Si nanosystems at different temperature ranges was proposed. In the temperature region of ~300–200 K charge carrier motion occurs through the n-Si with an employment of metallic clusters in pores being in a contact with the semiconductor, by means of the overbarrier emission of electrons from higher energy levels of Si conduction band. In the lower temperatures (~200-100 K) a current flow takes place only through the semiconductor due to an increase of resistivity on energy barriers n-Si/metal, which leads to a practically complete exclusion of a participation of the metal in the charge transport process. In the low temperatures (~100–20 K), the variable range hopping conduction between pores on the SiO2/Si boundary, containing localized states, dominates.